EL FUTURO DE LAS COMUNICACIONES EN LA SOCIEDAD: TENDECIAS Y AVANCES TECNOLÓGICOS QUE IMPACTARÁN EN LA COMUNICACIÓN - REYES PEREZ, KEVIN JOSUE (2024)
The purpose of this research work is to analyze the future of communications in society, the trends and technological advances that will impact on communication, evaluating the impact on interpersonal and mass communication processes, and analyzing the social, cultural and ethical implications of these advances. In such a way that for the execution of the same, prospective research was used in relation to a non-experimental design, in this sense, the qualitative research method was used, which is known for promoting the exploration, understanding and description of phenomena or groups of interest. The technique implemented for this research was the bibliographic review that allowed to know theoretical foundations from reliable sources, and to deepen in what refers to the future of communications in society, from the impact of technologies in this field. Bibliographic cards were used as instruments, which allowed the organization of the information collected, distinguishing the author, his argument and the year of publication as key aspects, which allowed to have a better notion of the subject and thus deduce more about it. A timeline was also elaborated with the purpose of showing in a chronological order, dates and important events as a visual way of representing the historical events, in a simplified way for a better understanding of the data and related events.